Constraint-induced aphasia therapy (CIAT): a randomised controlled trial in very early stroke rehabilitation. Issue 5 (3rd May 2016) - Ciccone, Natalie; West, Deborah; Cream, Angela; Cartwright, Jade; Rai, Tapan; Granger, Andrew; Hankey, Graeme J.; Godecke, Erin
Abstract : Background : Communication outcomes following stroke are improved when treatments for aphasia are administered early, within the first 3 months after stroke, and provided for more than 2 hours per week. However, uncertainty remains about the optimal type of aphasia therapy. Aims : We compared constraint-induced aphasia therapy (CIAT) with individual, impairment-based intervention, both administered early and daily after acute stroke. Methods & Procedures : This prospective, single-blinded, randomised, controlled trial recruited participants with mild to severe aphasia within 10 days of an acute stroke from acute/subacute Perth metropolitan hospitals ( n = 20). Participants were allocated by computer-generated block randomisation method to either the CIAT ( n = 12) or individual, impairment-based intervention group ( n = 8) delivered at the same intensity (45–60 min, 5 days a week) for 20 sessions over 5 weeks (15–20 hours total). The primary outcome, measured after completing the intervention, was the Aphasia Quotient (AQ) from the Western Aphasia Battery. Secondary outcomes were the AQ at 12 and 26 weeks post stroke, a Discourse Analysis (DA) score and the Stroke and Aphasia Quality of Life Scale (SAQoL), measured at therapy completion, 12 and 26 weeks post stroke. There was a 10% ( n = 2) dropout at the primary end point, both participants were in the CIAT group. The estimates for each treatment group were compared using repeated measures ANOVAs. Data from the 26-week follow-up assessment are presented, however, were not included in the between-group comparisons due to the low number of data points in each group. Outcomes & Results : Within groups analyses comparing performance at baseline, therapy completion, and 12 weeks post stroke revealed a statistically significant treatment effect for the AQ ( p < .001), DA ( p = .002), and SAQoL ( p < .001). Between groups analysis found there was no significant difference between the CIAT and individual therapy groups on any outcome measure. Conclusions : CIAT and individual therapy produced comparable amounts of change in the very early phase of recovery suggesting a standard, intensive daily dose of therapy within this period of recovery is feasible and beneficial. There were no significant differences between the two groups demonstrating that CIAT, which is provided in a group format, may be a viable option in the very early phase of aphasia recovery. The study highlights the need for further research into the impact of therapy type in very early aphasia therapy.